4-(4-Methoxyphenyl)naphtho[2,3-b]thiophene - G. Puthilibai; S. Vasudhevan; R. Joel Karunakaran (Acta Crystallographica Section E, 2012)
In the title compound, C19H14OS, the naphthothiophene moiety is almost planar except for the S atom of the five-membered ring, which is situated 0.047 (6) Å out of the C4 plane (with an r.m.s. deviation of fitted atoms = 0.0009 Å). The dihedral angle between the naphthothiophene plane and the attached methoxyphenyl ring is 67.6 (2)°. In the crystal, a C—H...π interaction is observed between a methoxyphenyl C—H group and the outer benzene ring of the naphthothiophene moiety. The five-membered ring of the naphthothiophene moiety is disordered, with the S and opposite non-fused C atom approximately exchanging positions, with a site-occupancy factors of 0.808 (3) and 0.187 (3).